Deciphering the mechanism of quercetin-Induced cell death in endothelial cells transformed by viral G protein-coupled receptor expression - Principe, Gabriel (2024)
Quercetin (QUE) is a natural flavonoid classified as a phytoestrogen due to its resemblance with human estrogens. Although its anticancer properties are well-known in various cancer models, its effect on viral-induced cancers has been less studied. Kaposi’s sarcoma (KS) is a virally induced cancer caused by Kaposi’s sarcoma-associated herpesvirus, which contains a constitutively activated viral G protein-coupled receptor (vGPCR) expressed during the viral lytic phase, leading to oncogenesis and angiogenesis through the activation of several signaling pathways. Our previous studies indicated that QUE inhibits vGPCR-mediated cell proliferation in vitro and tumor growth in vivo. In this work, we investigated the mechanism by which QUE exerts its antitumoral effects. QUE treatment (30 μM) for 24 h induced marked morphological changes in vGPCR cells consistent with apoptosis, including cell shrinkage and the formation of apoptotic bodies, as observed by scanning electron microscopy. In parallel experiments, a highly significant increase in cleaved caspase-3 protein levels was detected by Western blot analysis, further confirming apoptotic induction. To investigate oxidative stress, vGPCR cells were treated with QUE (5-45 μM) for 24 h or hydrogen peroxide (0.5 mM, 45 min) as a positive control, and intracellular oxidant levels were measured using the fluorogenic probe 2′,7′-dichlorofluorescin diacetate. QUE treatment led to a concentration-dependent increase in oxidant levels. Additionally, lipid peroxidation levels, evaluated by TBARS assay, were significantly increased by QUE (30 μM). Moreover, comet assay analysis of vGPCR cells treated with QUE (30 μM) for 48 h indicated a significant increase in DNA damage, evidenced by longer comet tails. Further exploration of signaling pathways by Western blot revealed that QUE (10-50 μM) for 48h increased p38 and ERK1/2 phosphorylation, whereas AKT phosphorylation remained unchanged. In conclusion, our findings suggest that QUE-induced oxidative stress and DNA damage may lead to apoptosis, with concurrent activation of stress-responsive signaling pathways (p38 and ERK1/2) potentially serving as adaptive responses to mitigate QUE’s cytotoxic effects